(untitled) (American Journal of Islam and Society, 2012)
Roger Scruton, known for his good-natured conservatism and general attempts to defend traditional Western life, seems blind to the novelty of our globalized world as he conflates Islam with radical Islam and attacks Muslims as though all were Islamists. Genial style notwithstanding, his indictment of Islam and Muslims is inaccurate and his desire to deny Muslims the right to live as Muslims in their own or Western polities anything but good-natured. Alas, until Muslims become secular and agree to imbibe alcohol, Scruton will reject them as impossibly asocial. He ignores that there are many faces of Islam varying in place and time as well as social milieu. That meshes with his devotion to viewing religious conviction through the lenses of bourgeois Western mores and deriding piety. Though appealing to populist sentiment, it does not rise to the standard of serious criticism or come near the scholarly obligation to give the arguments and the actions we oppose their strongest defense and then probe for what is weak ...